A STRATEGY TO MOTIVATE FRESHMAN AGRONOMY STUDENTS FOR THE USE OF APPLIED COMPUTING TECHNOLOGY - João E. M. Perea Martins; Eduardo Oyanedel; Manuel Flores Cabrales; Edvaldo José Scoton (European Journal of Agricultural and Rural Education, 2023)
This work objective is to propose a class activity that combines technological and agricultural aspects with the purpose of motivating freshmen students of agronomy to think about the use of computing technology applications in the agricultural area. The methodology was based on a 2-hour practical class in a computer lab where the students, most with no previous knowledge, use mathematical processing software to generate a color map of the temperature variation inside a greenhouse. This article shows step by step activity design, which can facilitate its reproduction even by professors without knowledge in this area of computing. Finally, this work proves qualitatively and quantitatively that its results were satisfactory to motivate the students to learn more about applied technology.